Activated alumina and its preparation method and application

Through the mixing of specific proportions of aluminum hydroxide and pseudo-boehmite and the rotating disk pelletizing method, combined with processes such as pressurization, oven, hydration, steam curing and gradient roasting, a product with high specific surface area, pore volume, Activated alumina balls with high strength and low wear rate solve the problem of poor performance of activated alumina balls in the existing technology and achieve efficient use in PSA systems.

CN118988245BActive Publication Date: 2025-01-24SHANGHAI JIUZHOU CHEM CO LTD

Patent Information

Application Number
CN202411481593.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

It is difficult to prepare activated alumina spheres with high specific surface area, pore volume, strength and low wear rate, especially when used in PSA systems for a long time, the adsorption capacity of activated alumina will decrease and the wear rate will be high.

Method used

By mixing the 75-80 weight hydroxide powder with 15-20 weights, a thin water aluminum and stone mixing, using a turntable to form a ball, and spray the binder to form active aluminum with a diameter of 1-3mm ball. Then pressurized and baked in the Maval furnace, and then hydrated and steam maintenance. Finally, the active aluminum alumina with excellent performance was prepared through gradient baking and evaporation.

Benefits of technology

The prepared activated alumina has a specific surface area ≥350m2/g, a pore volume ≥0.7cm3/g, a strength greater than 180N/grain, a wear rate ≤0.15%, and shows high compressive strength and long-term stability in the PSA system sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides an activated alumina and a preparation method and application thereof. The preparation method of activated alumina comprises the following steps: (1) mixing aluminum hydroxide mixed powder and pseudo-boehmite, placing the mixture in a ball-forming disk, balling the mixture by a rotating disk ball-forming method, spraying a binder during the ball-forming process, and preparing activated alumina balls with a diameter of 1-3 mm; (2) pressurizing the activated alumina balls to obtain pressurized activated alumina microspheres; (3) hydrating and steam curing the pressurized activated alumina balls; (4) gradient calcining the steam-cured activated alumina balls, soaking the calcined activated alumina balls in water for 60-65 hours, and then rotary evaporating the calcined activated alumina balls in a rotary evaporator at 85-90° C. and a rotation speed of 130-140 r / min to obtain activated alumina. The activated alumina balls prepared by the present invention have high specific surface area and pore volume, high strength, low wear rate, and good high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of desiccants, and in particular relates to activated alumina and a preparation method and application thereof. Background Art

[0002] Activated Alumina is a commonly used desiccant, widely used in industry and laboratories to remove moisture and other impurities from gases or liquids. Activated Alumina has a large specific surface area and pore structure, and can effectively adsorb moisture and other polar molecules. Considering the output, cost, performance control and other aspects of activated alumina, the turntable ball forming method has the largest output. The turntable ball forming method is one of the main methods for preparing spherical alumina. It mainly uses ordinary aluminum hydroxide as raw material and quickly dehydrates it in a high-temperature furnace to generate ρ-alumina.

[0003] The pores, pore volume and specific surface area of ​​activated alumina directly determine its adsorption and catalytic properties, while strength and attrition rate affect the service life of activated alumina. The higher the quality of alumina, the higher the preparation requirements for its pores, pore volume, specific surface area, strength and attrition rate. PSA (Pressure Swing Adsorption) is a commonly used gas separation and purification technology that uses the different adsorption capacities of adsorbents for gases at different pressures to separate and purify gases. In the PSA process, the selection of dry adsorbents is very important because it directly affects the gas purification effect and the operating efficiency of the equipment. As a commonly used PSA dry adsorbent, activated alumina may have some technical problems during long-term use, which may affect the performance of the adsorbent and the overall efficiency of the PSA system. Activated alumina may experience physical stress during repeated adsorption-desorption cycles, resulting in particle breakage or pulverization. At the same time, the adsorption capacity of activated alumina is greatly affected by temperature, and the adsorption capacity may decrease at high temperatures.

[0004] Therefore, how to prepare activated alumina balls with high specific surface area, pore volume, high strength and low wear rate has become a key issue that needs to be urgently solved in industrial production. Summary of the invention

[0005] The purpose of the present invention is to provide an activated alumina and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing activated alumina comprises the following steps:

[0008] (1) 75-80 parts by weight of aluminum hydroxide mixed powder and 15-20 parts by weight of pseudo-boehmite are mixed and placed in a ball-forming disk. The mixture is ball-formed by a rotating disk ball-forming method. During the ball-forming process, a binder is sprayed to form activated alumina balls with a diameter of 1-3 mm.

[0009] The aluminum hydroxide mixed powder comprises ultrafine aluminum hydroxide YTA-1 with a particle size of 1-2 μm, ultrafine aluminum hydroxide YTA-5 with a particle size of 4-6 μm and homemade aluminum hydroxide powder in a mass ratio of 1: (1.2-1.5): (0.3-0.6);

[0010] The method for preparing the homemade aluminum hydroxide powder comprises the following steps:

[0011] S1: dissolving sodium aluminate in water to obtain a sodium aluminate solution with a concentration of 4-6 mol / L;

[0012] S2: 3-isocyanate propyltrimethoxysilane, analytical pure magnesium oxide and N,N-dimethylformamide are mixed, stirred at 100-105°C for 2-3h, centrifuged, washed and dried to obtain silane-modified magnesium oxide; 10 parts by weight of silane-modified magnesium oxide are mixed with 50-60 parts by weight of ethanol, a mixture of nano-TiO2 and water is added dropwise, stirred at 60-65°C for 2-3h; centrifuged, washed and dried to obtain modified magnesium oxide;

[0013] S3: adding 100-120 g of modified magnesium oxide into 1 L of distilled water, and ultrasonicating for 3-4 min to obtain a modified magnesium oxide mixed solution, which is used as an initiating seed crystal;

[0014] S4: adding the modified magnesium oxide mixed solution to the sodium aluminate solution, heating and decomposing the solution at a temperature of 66-68° C. for 9-11 hours to obtain an aluminum hydroxide suspension; filtering, washing and drying the aluminum hydroxide suspension to obtain a self-made aluminum hydroxide powder;

[0015] (2) placing the activated alumina balls in a muffle furnace, pressurizing them under an air pressure of 1.0-1.5 MPa for 1-3 hours in a nitrogen atmosphere, and then baking them at 200-400° C. for 2-4 hours. After the muffle furnace is depressurized and cooled naturally, pressurized activated alumina microspheres are obtained;

[0016] (3) The pressurized activated alumina balls are completely immersed in water, hydrated at 25-30°C for 8-10 hours, and steam-cured for 3-5 hours.

[0017] (4) The activated alumina balls after steam curing are subjected to gradient calcination. The calcined activated alumina balls are immersed in water for 60-65 hours and then rotary evaporated in a rotary evaporator at 85-90°C and a rotation speed of 130-140 r / min to obtain activated alumina.

[0018] The present invention attempts to use commercially available aluminum hydroxide to prepare activated alumina, but the specific surface area of ​​the activated alumina obtained is not ideal. The present invention mixes two commercially available ultrafine aluminum hydroxides and homemade alumina in a specific ratio to improve the specific surface area of ​​the activated alumina. By mixing materials with different pore size distributions, the pore structure of the final activated alumina can be optimized and its specific surface area can be increased. The pore structure and grain size of homemade alumina can be used in conjunction with the advantages of ultrafine aluminum hydroxide to produce a synergistic effect and increase the specific surface area.

[0019] Furthermore, in step S2, the mass ratio of the silane-modified magnesium oxide to the nano-TiO2 is 10:(1-3).

[0020] Furthermore, in step S2, the weight ratio of 3-isocyanatepropyltrimethoxysilane, analytical grade magnesium oxide, and N,N-dimethylformamide is (1.0-1.2): (0.12-0.14): (40-50).

[0021] Furthermore, the volume of the modified magnesium oxide mixed solution added in step S4 accounts for 1-2% of the volume of the sodium aluminate solution.

[0022] Furthermore, the gradient calcination conditions in step (4) are as follows: first, at room temperature, the temperature is increased to 300-320°C at a heating rate of 70-80°C / h, and the temperature is kept at this temperature for 2-3h; then, the temperature is increased to 500-520°C at a heating rate of 100-120°C / h, and the temperature is kept at this temperature for 1.5-2.5h; finally, the temperature is increased to 600-650°C at a heating rate of 70-80°C / h, and the temperature is kept at this temperature for 1-2h.

[0023] The activated alumina prepared by conventional calcination methods has a high wear rate. By using the gradient calcination method of the present invention, the wear rate of activated alumina can be reduced. By controlling the change of calcination temperature, different grain sizes and pore structures can be formed inside the material. The grains formed by the calcination conditions of the present invention are smaller and the wear rate is lower.

[0024] Furthermore, the binder in step (1) is an aqueous solution of acetic acid with a mass percentage of 2-4%.

[0025] Furthermore, the pseudo-boehmite in step (1) comprises a mixture of pseudo-boehmite A, pseudo-boehmite B and pseudo-boehmite C in a weight ratio of 1: (1.2-1.4): (0.6-0.8); the particle size D50 of the pseudo-boehmite A is 13 μm, and the specific surface area is 245 m 2 / g, average pore volume 0.6cm 3 / g, average pore size of 6.8nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-11. Pseudo-boehmite B has a particle size D50 of 5μm and a specific surface area of ​​505m 2 / g, and the average pore volume is 1.15cm 3 / g, average pore size of 10.9nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-13. Pseudo-boehmite C has a particle size D50 of 50μm and a specific surface area of ​​265m 2 / g, average pore volume 0.4cm 3 / g, average pore size of 4-6nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-SB.

[0026] The present invention uses three kinds of pseudo-boehmite in a specific ratio to mix with aluminum hydroxide mixed powder, which can improve the compressive strength of activated alumina. The compounded pseudo-boehmite can provide more active sites. Aluminum hydroxide can form a complementary structure with the pseudo-boehmite during the mixing process. By mixing materials with different grain sizes, the grain size distribution of the final activated alumina can be optimized and the compressive strength can be improved. When pseudo-boehmite with specific performance parameters and homemade aluminum hydroxide prepared using a modified magnesium oxide mixed solution as an initiating seed are used, the activated alumina can be improved to maintain a high compressive strength when used as an adsorbent for PSA pressure swing adsorption hydrogen production. The structure of the activated alumina prepared under this condition is more stable, the ability to withstand the external environment is stronger, and the long-term use stability can be maintained.

[0027] The present invention provides activated alumina prepared by the preparation method, characterized in that the specific surface area of ​​the activated alumina is ≥350m 2 / g, pore volume ≥ 0.7cm 3 / g, strength greater than 180N / grain, abrasion rate ≤0.15%.

[0028] The invention provides application of activated alumina prepared by the preparation method.

[0029] Furthermore, the activated alumina is used to prepare a PSA dry adsorbent.

[0030] The invention provides application of the activated alumina.

[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0032] 1. The activated alumina prepared in the present invention is porous particles with uniform particle size, smooth surface, high mechanical strength, strong hygroscopicity, and does not swell or crack after absorbing water, but maintains its original shape.

[0033] 2. The present invention mixes two commercially available ultrafine aluminum hydroxides and homemade aluminum oxide in a specific ratio, which can improve the specific surface area of ​​activated aluminum oxide.

[0034] 3. The present invention can reduce the attrition rate of activated alumina by using the gradient calcination method of the present invention.

[0035] 4. The present invention uses three kinds of pseudo-boehmite in specific ratios to mix with aluminum hydroxide mixed powder, which can improve the compressive strength of activated alumina.

[0036] 5. The present invention can improve the compressive strength of activated alumina when used as an adsorbent for PSA pressure swing adsorption hydrogen production by using pseudo-boehmite with specific performance parameters and homemade aluminum hydroxide prepared using a modified magnesium oxide mixed solution as an initiating seed. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The raw materials used in the following examples of the present invention are all commercially available products:

[0039] Ultrafine aluminum hydroxide YTA-1 with a particle size of 1-2 μm and ultrafine aluminum hydroxide YTA-5 with a particle size of 4-6 μm were purchased from Jinan Jinyingtai Chemical Co., Ltd.

[0040] Sodium aluminate, purchased from Shandong Lier New Materials Co., Ltd., solid sodium aluminate No. 50.

[0041] Analytical grade magnesium oxide, Wuxi Zemei New Material Technology Co., Ltd., model ZH-ARL.

[0042] Example 1

[0043] This embodiment provides a method for preparing activated alumina, comprising the following steps:

[0044] (1) 78 parts by weight of aluminum hydroxide mixed powder and 17 parts by weight of pseudo-boehmite are mixed and placed in a ball-forming disk, and ball-formed by a rotating disk ball-forming method. During the ball-forming process, a binder is sprayed to form activated alumina balls with a diameter of 1-3 mm; the binder is an acetic acid aqueous solution with a mass percentage of 3%; the amount of the binder used is 35 parts by weight;

[0045] The aluminum hydroxide mixed powder comprises ultrafine aluminum hydroxide YTA-1 with a particle size of 1-2 μm, ultrafine aluminum hydroxide YTA-5 with a particle size of 4-6 μm, and homemade aluminum hydroxide powder in a mass ratio of 1:1.4:0.5;

[0046] (2) placing the activated alumina balls in a muffle furnace, pressurizing them at an air pressure of 1.2 MPa for 2 h in a nitrogen atmosphere, and then baking them at 300 °C for 3 h. After the muffle furnace was depressurized and cooled naturally, pressurized activated alumina microspheres were obtained;

[0047] (3) The pressurized activated alumina balls are completely immersed in water, hydrated at 28°C for 9 hours, and steam-cured for 4 hours.

[0048] (4) The activated alumina balls after steam curing were subjected to gradient calcination. The conditions of the gradient calcination were as follows: first, the temperature was increased to 310°C at a heating rate of 75°C / h at room temperature, and the temperature was kept at that temperature for 2.5 h. Then, the temperature was increased to 510°C at a heating rate of 110°C / h, and the temperature was kept at that temperature for 2 h. Finally, the temperature was increased to 620°C at a heating rate of 75°C / h, and the temperature was kept at that temperature for 1.5 h. After the calcined activated alumina balls were immersed in water for 62 h, they were rotary evaporated in a rotary evaporator at 87°C and a rotation speed of 135 r / min to obtain activated alumina.

[0049] The method for preparing the homemade aluminum hydroxide powder comprises the following steps:

[0050] S1: dissolving sodium aluminate in water to obtain a sodium aluminate solution with a concentration of 5 mol / L;

[0051] S2: 3-isocyanate propyl trimethoxysilane, analytical pure magnesium oxide and N, N-dimethylformamide were mixed, and the weight ratio of 3-isocyanate propyl trimethoxysilane, analytical pure magnesium oxide and N, N-dimethylformamide was 1.1:0.13:45; stirred at 102°C for 2.5h, centrifuged, washed and dried to obtain silane-modified magnesium oxide; 10 parts by weight of silane-modified magnesium oxide and 55 parts by weight of ethanol were mixed, and a mixture of nano-TiO2 and water was added dropwise, stirred at 62°C for 2.5h; centrifuged, washed and dried to obtain modified magnesium oxide; the mass ratio of silane-modified magnesium oxide to nano-TiO2 was 10:3. The mass percentage of nano-TiO2 in the mixture of nano-TiO2 and water was 2.7wt%. Nano-TiO2 was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd., model ZT05.

[0052] S3: adding 110 g of modified magnesium oxide to 1 L of distilled water, and ultrasonicating for 4 min to obtain a modified magnesium oxide mixed solution, which is used as an initiating seed crystal;

[0053] S4: adding a modified magnesium oxide mixed solution to the sodium aluminate solution, wherein the volume of the modified magnesium oxide mixed solution accounts for 1.5% of the volume of the sodium aluminate solution, heating to decompose, the decomposition temperature is 67° C., and the decomposition time is 10 hours to obtain an aluminum hydroxide suspension; filtering, washing, and drying the aluminum hydroxide suspension to obtain a self-made aluminum hydroxide powder;

[0054] The pseudo-boehmite comprises a mixture of pseudo-boehmite A, pseudo-boehmite B and pseudo-boehmite C in a weight ratio of 1:1.3:0.7; the particle size D50 of the pseudo-boehmite A is 13 μm, and the specific surface area is 245 m 2 / g, average pore volume 0.6cm 3 / g, average pore size of 6.8nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-11. Pseudo-boehmite B has a particle size D50 of 5μm and a specific surface area of ​​505m 2 / g, and the average pore volume is 1.15cm 3 / g, average pore size of 10.9nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-13. Pseudo-boehmite C has a particle size D50 of 50μm and a specific surface area of ​​265m 2 / g, average pore volume 0.4cm 3 / g, average pore size of 4-6nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-SB.

[0055] Example 2

[0056] This embodiment provides a method for preparing activated alumina, comprising the following steps:

[0057] (1) 75 parts by weight of aluminum hydroxide mixed powder and 20 parts by weight of pseudo-boehmite are mixed and placed in a ball-forming disk, and ball-formed by a rotating disk ball-forming method. During the ball-forming process, a binder is sprayed to form activated alumina balls with a diameter of 1-3 mm; the binder is an acetic acid aqueous solution with a mass percentage of 2%; the amount of the binder used is 30 parts by weight;

[0058] The aluminum hydroxide mixed powder comprises ultrafine aluminum hydroxide YTA-1 with a particle size of 1-2 μm, ultrafine aluminum hydroxide YTA-5 with a particle size of 4-6 μm, and homemade aluminum hydroxide powder in a mass ratio of 1:1.2:0.6;

[0059] (2) placing the activated alumina balls in a muffle furnace, pressurizing them at an air pressure of 1.0 MPa for 3 h in a nitrogen atmosphere, and then baking them at 200 °C for 4 h. After the muffle furnace is depressurized and cooled naturally, pressurized activated alumina microspheres are obtained;

[0060] (3) The pressurized activated alumina balls are completely immersed in water, hydrated at 25°C for 8 hours, and steam-cured for 5 hours.

[0061] (4) The activated alumina balls after steam curing were subjected to gradient calcination. The conditions of the gradient calcination were as follows: first, the temperature was increased to 300°C at a heating rate of 80°C / h at room temperature, and the temperature was kept at that temperature for 3 h. Then, the temperature was increased to 520°C at a heating rate of 100°C / h, and the temperature was kept at that temperature for 2.5 h. Finally, the temperature was increased to 650°C at a heating rate of 70°C / h, and the temperature was kept at that temperature for 1 h. After the calcined activated alumina balls were immersed in water for 65 h, they were rotary evaporated in a rotary evaporator at 85°C and a rotation speed of 140 r / min to obtain activated alumina.

[0062] The method for preparing the homemade aluminum hydroxide powder comprises the following steps:

[0063] S1: dissolving sodium aluminate in water to obtain a sodium aluminate solution with a concentration of 4 mol / L;

[0064] S2: 3-isocyanate propyl trimethoxysilane, analytical pure magnesium oxide and N, N-dimethylformamide were mixed, and the weight ratio of 3-isocyanate propyl trimethoxysilane, analytical pure magnesium oxide and N, N-dimethylformamide was 1.2:0.12:40; stirred at 100°C for 3h, centrifuged, washed and dried to obtain silane-modified magnesium oxide; 10 parts by weight of silane-modified magnesium oxide and 50 parts by weight of ethanol were mixed, and a mixture of nano-TiO2 and water was added dropwise, stirred at 65°C for 2h; centrifuged, washed and dried to obtain modified magnesium oxide; the mass ratio of silane-modified magnesium oxide to nano-TiO2 was 10:1. The mass percentage of nano-TiO2 in the mixture of nano-TiO2 and water was 2.5wt%. Nano-TiO2 was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd., model ZT05.

[0065] S3: adding 100 g of modified magnesium oxide into 1 L of distilled water, and ultrasonicating for 3 min to obtain a modified magnesium oxide mixed solution, which is used as an initiating seed crystal;

[0066] S4: adding a modified magnesium oxide mixed solution to the sodium aluminate solution, wherein the volume of the modified magnesium oxide mixed solution accounts for 1% of the volume of the sodium aluminate solution, heating for decomposition, the decomposition temperature is 66° C., and the decomposition time is 11 hours to obtain an aluminum hydroxide suspension; filtering, washing, and drying the aluminum hydroxide suspension to obtain a self-made aluminum hydroxide powder;

[0067] The pseudo-boehmite comprises a mixture of pseudo-boehmite A, pseudo-boehmite B and pseudo-boehmite C in a weight ratio of 1:1.2:0.6; the particle size D50 of the pseudo-boehmite A is 13 μm, and the specific surface area is 245 m 2 / g, average pore volume 0.6cm 3 / g, average pore size of 6.8nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-11. Pseudo-boehmite B has a particle size D50 of 5μm and a specific surface area of ​​505m2 / g, and the average pore volume is 1.15cm 3 / g, average pore size of 10.9nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-13. Pseudo-boehmite C has a particle size D50 of 50μm and a specific surface area of ​​265m 2 / g, average pore volume 0.4cm 3 / g, average pore size of 4-6nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-SB.

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 1 is that the aluminum hydroxide mixed powder includes ultrafine aluminum hydroxide YTA-1 with a particle size of 1-2 μm, ultrafine aluminum hydroxide YTA-5 with a particle size of 4-6 μm and homemade aluminum hydroxide powder in a mass ratio of 1:1:1.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 1 is that the aluminum hydroxide mixed powder is replaced by ultrafine aluminum hydroxide YTA-1 with a particle size of 1-2 μm.

[0072] Comparative Example 3

[0073] The difference between this comparative example and Example 1 is that the analytically pure magnesium oxide is not modified.

[0074] The method for preparing the homemade aluminum hydroxide powder comprises the following steps:

[0075] S1: dissolving sodium aluminate in water to obtain a sodium aluminate solution with a concentration of 5 mol / L;

[0076] S2: 110 g of analytical pure magnesium oxide was added to 1 L of distilled water and ultrasonicated for 4 min to obtain a magnesium oxide mixed solution, which was used as an initiating seed crystal;

[0077] S3: After heating the sodium aluminate solution, add the mixed solution of magnesium oxide to a volume of 1.5% of the volume of the sodium aluminate solution, heat to decompose, the decomposition temperature is 67° C., the decomposition time is 10 hours, and an aluminum hydroxide suspension is obtained; the aluminum hydroxide suspension is filtered, washed, and dried to obtain a homemade aluminum hydroxide powder.

[0078] Comparative Example 4

[0079] The difference between this comparative example and Example 1 is that the gradient calcination conditions in step (4) are: first calcining at room temperature at a heating rate of 100°C / h for 5.5h, and then calcining at 550°C for 4h.

[0080] Comparative Example 5

[0081] The difference between this comparative example and Example 1 is that the pseudo-boehmite comprises a mixture of pseudo-boehmite A, pseudo-boehmite B and pseudo-boehmite C in a weight ratio of 1:1:1.

[0082] Comparative Example 6

[0083] The difference between this comparative example and Example 1 is that the pseudo-boehmite comprises a mixture of pseudo-boehmite A, pseudo-boehmite B and pseudo-boehmite C in a weight ratio of 1:1.3:0.7; the particle size D50 of the pseudo-boehmite A is ≤15 μm, and the specific surface area is ≥230 m 2 / g, average pore volume is 0.5-0.8cm 3 / g, average pore size of 5-10nm, purchased from Yangzhou Zhongtianli New Materials Co., Ltd., model AZTL-CAH-1. Pseudo-boehmite B has a particle size D50≤15μm and a specific surface area ≥280m 2 / g, average pore volume of 0.9-1.1cm 3 / g, average pore size of 10-15nm, purchased from Yangzhou Zhongtianli New Materials Co., Ltd., model ZTL-CAH-3. Pseudo-boehmite C has a particle size D50 of 12μm and a specific surface area of ​​234m 2 / g, average pore volume 1.25cm 3 / g, average pore size of 15.9 nm, purchased from Harbin Yinyi Technology Co., Ltd., model: YY-12.

[0084] Performance Testing

[0085] 1. Performance tests were performed on the activated alumina of Examples 1-2 and Comparative Examples 1-6.

[0086] 10 particles of activated alumina prepared in Examples 1-2 and Comparative Examples 1-6 were randomly selected, and the compressive strength was measured using a strength tester. The maximum and minimum values ​​were removed, and the average value of the remaining 8 groups of data was taken as the compressive strength.

[0087] 2. The activated alumina of Examples 1-2 and Comparative Examples 1-6 was used as an adsorbent for PSA pressure swing adsorption hydrogen production, and the activated alumina was continuously used until the hydrogen production amount reached 20,000 Nm 3 After that, the compressive strength of activated alumina was determined using the same method as above.

[0088] The wear rate is determined according to the method for measuring wear rate in 6.10 of HG / T3927-2020.

[0089]

[0090] From the above performance test results, it can be seen that the specific surface area of ​​the activated alumina in Example 1-2 is ≥350m 2 / g, pore volume ≥ 0.7cm 3 / g, strength greater than 180N / grain, abrasion rate ≤0.15%. In particular, the comprehensive performance of Example 1 is the most outstanding.

[0091] However, the comparative examples were significantly inferior to the embodiments in the corresponding performance tests because they did not adopt the necessary technical solutions. In comparative examples 1 and 2, the composition of the aluminum hydroxide mixed powder was changed, and it can be seen that the specific surface area decreased. In comparative example 3, the modification scheme of analytically pure magnesium oxide was not used. From the results, it can be seen that the structure of the homemade aluminum hydroxide was affected, which further led to a decrease in the compressive strength of the activated alumina when used as an adsorbent for PSA pressure swing adsorption hydrogen production. The roasting conditions of comparative example 4 were changed, and the wear rate increased. In comparative example 5, the ratio of pseudo-boehmite was different, and the compressive strength of the obtained activated alumina decreased. In comparative example 6, the performance parameters of pseudo-boehmite were changed, and the compressive strength of the activated alumina decreased when used as an adsorbent for PSA pressure swing adsorption hydrogen production. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0092] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing activated alumina, characterized in that: The following steps are involved: (1) 75-80 parts by weight of aluminum hydroxide mixed powder and 15-20 parts by weight of pseudo-boehmite are mixed and placed in a ball-forming disk. The mixture is ball-formed by a rotating disk ball-forming method. During the ball-forming process, a binder is sprayed to form active microspheres with a diameter of 1-3 mm. The aluminum hydroxide mixed powder comprises ultrafine aluminum hydroxide YTA-1 with a particle size of 1-2 μm, ultrafine aluminum hydroxide YTA-5 with a particle size of 4-6 μm and homemade aluminum hydroxide powder in a mass ratio of 1: (1.2-1.5): (0.3-0.6); The method for preparing the homemade aluminum hydroxide powder comprises the following steps: S1: dissolving sodium aluminate in water to obtain a sodium aluminate solution with a concentration of 4-6 mol / L; S2: 3-isocyanate propyltrimethoxysilane, analytical pure magnesium oxide and N,N-dimethylformamide are mixed, stirred at 100-105°C for 2-3h, centrifuged, washed and dried to obtain silane-modified magnesium oxide; 10 parts by weight of silane-modified magnesium oxide are mixed with 50-60 parts by weight of ethanol, a mixture of nano-TiO2 and water is added dropwise, stirred at 60-65°C for 2-3h; centrifuged, washed and dried to obtain modified magnesium oxide; S3: adding 100-120 g of modified magnesium oxide into 1 L of distilled water, and ultrasonicating for 3-4 min to obtain a modified magnesium oxide mixed solution, which is used as an initiating seed crystal; S4: adding the modified magnesium oxide mixed solution to the sodium aluminate solution, heating and decomposing the solution at a temperature of 66-68° C. for 9-11 hours to obtain an aluminum hydroxide suspension; filtering, washing and drying the aluminum hydroxide suspension to obtain a self-made aluminum hydroxide powder; (2) placing the active microspheres in a muffle furnace, pressurizing them under an air pressure of 1.0-1.5 MPa for 1-3 hours in a nitrogen atmosphere, and then baking them at 200-400° C. for 2-4 hours. After the muffle furnace is depressurized and cooled naturally, pressurized activated alumina microspheres are obtained; (3) completely immersing the pressurized activated alumina microspheres in water, hydrating them at 25-30°C for 8-10 hours, and steam curing the hydrated activated alumina microspheres for 3-5 hours; (4) The activated alumina microspheres after steam curing are subjected to gradient calcination. After the calcined activated alumina microspheres are immersed in water for 60-65 hours, they are rotary evaporated in a rotary evaporator at 85-90° C. and a rotation speed of 130-140 r / min to obtain activated alumina; The mass ratio of silane-modified magnesium oxide to nano-TiO2 in step S2 is 10:(1-3); The weight ratio of 3-isocyanatepropyltrimethoxysilane, analytical grade magnesium oxide, and N,N-dimethylformamide in step S2 is (1.0-1.2): (0.12-0.14): (40-50); In step S4, the volume of the modified magnesium oxide mixed solution accounts for 1-2% of the volume of the sodium aluminate solution; The conditions for the gradient calcination in step (4) are: first, at room temperature, the temperature is increased to 300-320°C at a heating rate of 70-80°C / h, and the temperature is kept at this temperature for 2-3h, then the temperature is increased to 500-520°C at a heating rate of 100-120°C / h, and the temperature is kept at this temperature for 1.5-2.5h, and finally the temperature is increased to 600-650°C at a heating rate of 70-80°C / h, and the temperature is kept at this temperature for 1-2h; The binder in step (1) is an aqueous solution of acetic acid with a mass percentage of 2-4%; The pseudo-boehmite in step (1) comprises pseudo-boehmite A, pseudo-boehmite B and pseudo-boehmite C in a weight ratio of 1: (1.2-1.4): (0.6-0.8); the particle size D50 of pseudo-boehmite A is 13 μm, and the specific surface area is 245 m 2 / g, average pore volume 0.6cm 3 / g, average pore size is 6.8nm; the particle size D50 of pseudo-boehmite B is 5μm, and the specific surface area is 505m 2 / g, and the average pore volume is 1.15cm 3 / g, average pore size is 10.9nm; the particle size D50 of pseudo-boehmite C is 50μm, and the specific surface area is 265m 2 / g, average pore volume 0.4cm 3 / g, the average pore size is 4-6nm.

2. An activated alumina prepared by the preparation method according to claim 1, characterized in that: The specific surface area of ​​activated alumina is ≥350m 2 / g, pore volume ≥ 0.7cm 3 / g, strength greater than 180N / grain, abrasion rate ≤0.15%.

3. An application of the activated alumina according to claim 2, characterized in that: The activated alumina is used to prepare PSA dry adsorbent.

Citation Information

Patent Citations

  • Preparation method of high-performance activated alumina ball

    CN106745121A

  • Aluminum oxide carrier and preparation method and application thereof

    CN109569740A

Cited By

  • Preparation method of high-strength activated aluminum oxide for drying agent

    CN121755155A